DESIGN, MANUFACTURING AND TESTING KINETIC ADSORPTION TEST RIG - Abrar Ridwan; Nasruddin -; Awaludin Martin; Arfie I. Firmansyah (Sistem Informasi, 2011)
Adsorption on a solid adsorbent is the fundamental processes in the field of separation processes, purification of gases, adsorption cooling, advanced adsorption cooling, and extensive work on hydrogen storage. The understanding of the thermodynamic properties of adsorbent plus adsorbate system is important to analyze. Information concerning the relevant adsorption equilibrium and characterized of adsorbent is generally an essential requirement for the analysis and design of an adsorption separation process. For practical application, theadsorption equilibrium must be known over a broad range of operation temperatures. Also, the isotherms of pure species are fundamental information for dynamic simulation of adsorbers. The main objective of this research is to design kinetic adsorption test rig to investigate the capacity and rate of adsorption on adsorbent and adsorbate pair’s. The result of design kinetic adsorption test rig including dimensions of vapor vessel (pressure vessel) and measuring cell. The volume of vapour vessel is 1000 ml and measuring cell is 100 ml. Kinetic adsorption test rig was manufactured to investigate capacity and rate of adsorption up to 40 bar.